Human adult stem cells from diverse origins: An overview from multiparametric immunophenotyping to clinical applications. Issue 1 (25th November 2013) - Sousa, Bruna R.; Parreira, Ricardo C.; Fonseca, Emerson A; Amaya, Maria J.; Tonelli, Fernanda M. P.; Lacerda, Samyra M. S. N.; Lalwani, Pritesh; Santos, Anderson K.; Gomes, Katia N.; Ulrich, Henning; Kihara, Alexandre H.; Resende, Rodrigo R.
Abstract Stem cells are known for their capacity to self‐renew and differentiate into at least one specialized cell type. Mesenchymal stem cells (MSCs) were isolated initially from bone marrow but are now known to exist in all vascularized organ or tissue in adults. MSCs are particularly relevant for therapy due to their simplicity of isolation and cultivation. The International Society for Cellular Therapy (ISCT) has proposed a set of standards to define hMSCs for laboratory investigations and preclinical studies: adherence to plastic in standard culture conditions; in vitro differentiation into osteoblasts, adipocytes, and chondroblasts; specific surface antigen expression in which ≥95% of the cells express the antigens recognized by CD105, CD73, and CD90, with the same cells lacking (≤2% positive) the antigens CD45, CD34, CD14 or CD11b, CD79a or CD19, and HLA‐DR. In this review we will take an historical overview of how umbilical cord blood, bone marrow, adipose‐derived, placental and amniotic fluid, and menstrual blood stem cells, the major sources of human MSC, can be obtained, identified and how they are being used in clinical trials to cure and treat a very broad range of conditions, including heart, hepatic, and neurodegenerative diseases. An overview of protocols for differentiation into hepatocytes, cardiomyocytes, neuronal, adipose, chondrocytes, and osteoblast cells are highlighted. We also discuss a new source of stem cells, induced pluripotent stem cells (iPS cells) and some pathways, which are common to MSCs in maintaining their pluripotent state. © 2013 International Society for Advancement of Cytometry